2021
DOI: 10.3390/molecules26195803
|View full text |Cite
|
Sign up to set email alerts
|

Natural Polyphenols as Immunomodulators to Rescue Immune Response Homeostasis: Quercetin as a Research Model against Severe COVID-19

Abstract: The COVID-19 pandemic is caused by SARS-CoV-2 and is leading to the worst health crisis of this century. It emerged in China during late 2019 and rapidly spread all over the world, producing a broad spectrum of clinical disease severity, ranging from asymptomatic infection to death (4.3 million victims so far). Consequently, the scientific research is devoted to investigating the mechanisms of COVID-19 pathogenesis to both identify specific therapeutic drugs and develop vaccines. Although immunological mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 122 publications
(176 reference statements)
1
20
0
1
Order By: Relevance
“…In addition, some Physalin derivatives have very recently been introduced as potent M pro inhibitors (78,134,135) and Hinokiflavone which belongs to biflavonoid compounds, has already been identified as the antiviral potential of H1N1 influenza inhibitor (55). Even more interesting is the fact that, 5 out of 13 phytochemicals -two flavonoid glycosides (6 and 7 in Figure 2), two biflavonoid compounds (8 and 13), and Pongamoside A (11)contain the flavonoid scaffold which is well-known for its striking antiviral potential against diverse coronaviruses (9,55,60,63,(66)(67)(68)(69)71,76,(82)(83)(84)87). Two compounds 1 (a steroidal lactone) and 10 have also been proposed as dual inhibitors targeting both the Spike RBD and M pro proteins (68,72,78,136,137).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some Physalin derivatives have very recently been introduced as potent M pro inhibitors (78,134,135) and Hinokiflavone which belongs to biflavonoid compounds, has already been identified as the antiviral potential of H1N1 influenza inhibitor (55). Even more interesting is the fact that, 5 out of 13 phytochemicals -two flavonoid glycosides (6 and 7 in Figure 2), two biflavonoid compounds (8 and 13), and Pongamoside A (11)contain the flavonoid scaffold which is well-known for its striking antiviral potential against diverse coronaviruses (9,55,60,63,(66)(67)(68)(69)71,76,(82)(83)(84)87). Two compounds 1 (a steroidal lactone) and 10 have also been proposed as dual inhibitors targeting both the Spike RBD and M pro proteins (68,72,78,136,137).…”
Section: Resultsmentioning
confidence: 99%
“…During the COVID-19 pandemic, several herbal compound databases derived from the medicinal plants of various geographical regions, such as China (65,69,(73)(74)(75)(76), India (68,77), Vietnam (78), Korea (65), Jordan (79), Africa (80), and Brazil (81) have been evaluated, both computationally and experimentally, for their potential antiviral activities against the SARS-CoV-2. Accordingly, it has been reported that multiple phytochemicals from various compound classes, including polyphenols (55,60,62,63,68,78,(82)(83)(84), alkaloids (57,63,(66)(67)(68)(69)85), terpenes (55,63,66,67,69,84,86) and flavonoids (9,55,60,63,(66)(67)(68)(69)71,76,(82)…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenols are naturally occurring compounds with immunomodulatory activity, and have a potential role in reducing inflammation and preventing the onset of the more serious symptoms of certain chronic diseases. Some clinical trials with polyphenols, most notably quercetin, for the treatment of COVID-19 have been approved, with some interesting results [66].…”
Section: Other Immunomodulatorsmentioning
confidence: 99%
“…In summary, accumulating evidence deriving from both computational and experimental studies suggests that quercetin, as other phenolic compounds, can act at multiple levels to inhibit or reduce the infectivity of coronaviruses including SARS‐CoV and SARS‐CoV‐2 although only very recently the clinical efficacy of these treatments have been explored (Bernini & Velotti, 2021 ; Di Pierro, Derosa, et al, 2021 ; Di Pierro, Iqtadar, et al, 2021 ; Rondanelli et al, 2022 ; Shohan et al, 2022 ).…”
Section: Anti‐ Severe Acute Respiratory Syndrome Coronavirus‐2 ( ...mentioning
confidence: 99%
“…The broad array of quercetin medicinal properties suggests possible clinical efficacy in Coronavirus disease-19 (COVID-19) (Bernini & Velotti, 2021;Derosa et al, 2021;Di Pierro, Derosa, et al, 2021;Di Pierro, Iqtadar, et al, 2021;Shohan et al, 2022) with comorbidities like hypertension, diabetes mellitus, obesity, Chronic obstructive pulmonary disease (COPD), coagulopathy and cytokine storm, all conditions emerging as a potential cause of severity and fatality among COVID-19 patients (Xu et al, 2020;Zhang et al, 2020). In preparing the present narrative review, data from PubMed, Scopus, EMBASE, Web of Science, Cochrane library, and Google Scholar databases have been retrieved to identify relevant studies concerning quercetin, flavonoids, COVID-19, and the above-mentioned pathologies.…”
Section: Introductionmentioning
confidence: 99%